FEMINIST THEORY: AN INTEGRATED REVIEW OF WAVES, PARADIGMS, AND GLOBAL PERSPECTIVES - Asnath Naftali Remtulla; Vina Salviana Darvina Soedarwo; Tri Sulistyaningsih; Rinikso Moelia Kartono (SOSIOEDUKASI, 2026)
This paper gives critical analytical overview of the feminist theories focusing on their development over time, ideological components, and critical discussions. The paper traces four major waves of feminist thought, and examines fourteen Feminism schools of thought includes liberal, radical, Marxist and socialist, Black, postcolonial, psychoanalytic, postmodern feminism, ecofeminism, transnational feminism, intersectional, cultural, existential, Islamic and digital. Both theoretical strands result of particular historical circumstances and intellectual cultures, focused on different aspects of gender oppression, power, identity, and social justice. Discussion shows shift of feminist theory to legal, political equality and intersectional forms of oppression includes race, class, sexuality, colonialism and digital capitalism. Based on the major feminist scholars and theories, analysis reveals feminist movements upheld evolving social, economic, and political situations. Paper highlights shortcomings of feminist discourse and address the means of localized and inclusive especially Global South. Paper synthesizes classical and modern feminist thought, which proves useful in gaining a better understanding that feminism is a dynamic and transforming body of knowledge, aimed disrupting structural inequalities and encouraging gender justice. The study finds, feminism theories are analytical concepts that could be used to analyze relations of power and social change in various cultural settings.